Sufism and the scriptures: metaphysics and sacred history in the thought of 'Abd al-Karı̂m al-Jı̂lı̂ - Morrissey, Fitzroy (I.B. Tauris, 2020)
1. Introduction -- 2. The Qur'an -- 3. The Torah -- 4. The Psalms -- 5. The Gospel -- 6. Conclusion